Parents Matter: Associations of Parental BMI and Feeding Behaviors With Child BMI in Brazilian Preschool and School-Aged Children - Warkentin, Sarah; Mais, Laís A.; Latorre, Maria do Rosário Dias de Oliveira; Carnell, Susan; Taddei, José Augusto de Aguiar Carrazedo (Frontiers in Nutrition, 2018)
Background: Brazil is undergoing nutritional transition and rates of obesity in preschool and school-aged children are increasing. Excess weight in the first years of life could predict excess weight in adulthood, making risk factors essential to study in this population. Objective: Our goal was to investigate associations of parent feeding behaviors, as well as more distal familial influences including family SES and maternal and paternal weight, with BMI z- score in preschool and school-aged children in a Brazilian sample. Methods: Cross-sectional study. Data were collected in 14 Brazilian private schools. Parents of children aged 2-8 years (n=1071) completed a questionnaire assessing parent feeding behaviors, as well as sociodemographic and anthropometric information. Hierarchical linear regression models were fitted to investigate relationships between parent and child characteristics and child BMI z in preschool (2-5 years, n=397) and school-aged (6-8 years, n=618) children. Results: Final models indicated that higher mother BMI and ‘restriction for weight control’ were associated with higher child BMI z-score in both age groups (excessive weight in preschoolers and school-aged children: 24.4% and 35.9%, respectively). In preschoolers only, ‘healthy eating guidance’ and ‘pressure’ were associated with lower child BMI z-score. For school-aged children, male sex, higher father BMI, and ‘restriction for health’ were associated with higher child BMI z. Conclusions: Parent feeding behaviors and parent weight, as well as child sex, are associated with child BMI z, with evidence for differential relationships in preschool and school-aged children. Optimal obesity prevention and treatment strategies may differ by child age.